Briskness index of black tea based on arrangement technique of brewing period - Dadan Rohdiana; Shabri Shabri (Jurnal Penelitian Teh dan Kina, 2014)
Research of briskness index of black tea base on arrangement technique brewing period has been done. The aim of this research is to find the best brewing periode arrangement technique which indicated the height of briskness index by determine of theaflavin and caffeine content. Result of this research shown that brewing periode arrangement for 12 minutes initiated brewing for 3 minutes has the highest of briskness index, i.e. 22.71 with theaflavin and caffeine content were 0,29% and 0,97% dry basis respectively. In contras, brewing periode arrangement technique for 3 minutes initiated by brewing periode 12 and 6 minutes respectively were liquor with the lowest of briskness index i.e. 13.73 with theaflavin and caffeine content were 0.10% and 0.66% dry basis respectively. This research concluded that black tea could be brewed until 3 times.